Institutional Ethos, Peers and Individual Outcomes - David J. Zimmerman; David Rosenblum; Preston Hillman (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2004)
In this paper we present estimates of roommate and institution based peer effects. Using data from the College & Beyond survey, the Freshman survey, and phonebook data that allows us to identify college roommates - we estimate models of students' political persuasion and intellectual engagement. The evidence suggests that a student's roommate's political sentiments have some impact on their own political views later in life. We also implement a cluster based analysis that attempts to answer the question: how would a student's outcomes have changed if they'd attended a very different school? Our findings suggest that student outcomes are, indeed, sensitive to the school they attend. Similar students attending schools that have a decidedly different 'ethos' differ in important ways post-college. Institutional peer effects seem to have a powerful effect on student outcomes.
Keywords: 330; Meinung; Soziale Integration; Studium; Schätzung; USA; peer effects